Ana's story : a journey of hope - Bush, Jenna; Baxter, Mia (New York, NY : HarperCollins Publishers, 2007)
The author reveals the life of a young woman she met while on an internship with UNICEF and how, despite living with HIV and losing her family to AIDS, she is thriving and looking forward to giving her child a better life.
Ana's story -- Afterword -- Letter from Jenna Bush -- You can make a difference -- Protect yourself, protect others -- Websites and help lines -- What's the real deal?: Ten Myths about HIV/AIDS -- Do you know the whole story?: Ten myths about abuse -- Discussion questions for Ana's Story.
Keywords: Ana -- Juvenile literature; AIDS (Disease) in adolescence -- Biography; HIV-positive persons -- Biography